Rekabentuk dan pembangunan sistem pakar pengauditan berkomputer : kajian kes di UTM - Mohamed Sidek, Zailani (Penerbit UTM Press, 1990)
This article is a part one of the project on the design and development of an computer auditing expert system for UTM. Due to the fact that the field of computer auditing is new not only to the society in UTM, but also in Malaysia in general, this article has started off by explaining the concepts involved in computer auditing. The article further discussed in brief the issues involved in computer auditing and its evolution with respect to the fast development in the field of computer science and technology. The project involve the use of expert system shell. As such, the concepts, principles and components of expert systems has been introduced. In particular, the problems, life-cycle and challenges faced in the design has been mentioned.